Research methods in communication research / Abdul Rauf Ridzuan, Abdul Rahim Ridzuan and Mardhiyah Ridzuan - Ridzuan, Abdul Rauf; Ridzuan, Abdul Rahim; Ridzuan, Mardhiyah (Faculty of Communication & Media Studies, 2018)
Research is collecting data. It is also known as the systematic approach to obtaining and confirming new and reliable knowledge”. It is also a systematic and orderly (following a series of steps). The purpose is new knowledge, which must be reliable. As stated by Baxter and Babbie (2003), research is the systematic effort to secure answers to questions. Research questions deal with issues requiring data and information. This article gives an outline of research methods that were followed in the study. It provides information on the participants, that is, the criteria for inclusion in the study, who the participants were and how they were sampled. The researcher describes the research design that was chosen for the purpose of this study and the reasons for this choice. The instrument that was used for data collection is also described and the procedures that were followed to carry out this study are included. The researcher also discusses the methods used to analyse the data. Lastly, this paper will help researcher to explain how to choose the proper method and will guide researchers to write their methodology in academically.